(untitled) (Veterinária Notícias, 2022)
The testudines are members of the Reptilia class, they are ectothermic and differ from other reptiles by the presence of the shell, which covers most of their bodies. Shell fractures are common in these animals and can occur due to several factors, mainly trauma. This paper aims to report the use of a prosthesis in a red-footed tortoise (Chelonoidis carbonarius). An adult female weighing 2.45 kg was sent to the Setor de Animais Silvestres of Veterinary Hospital of Universidade de Brasília. The specimen presented a carapace fracture caused by compress of garbage truck. Even after the healing of the lesion, there was persistence communication between the celomatic cavity and the environment, which caused recurrent pneumonia. After stabilization of the patient and treatment of infections, an adhesive cover was placed to isolate the cellomic cavity, which was changed periodically. Moreover, it was decided to make a prosthesis with acrylic resin, since it was not feasible to perform the repair by conventional methods. The method was satisfactory in the sealing of the carapace and the animal was monitored for a month without showing signs of pneumonia or any other complications.